028 Adjunctive intraarterial thrombolysis in endovascular clot retrieval: a systematic review and meta-analysis. (23rd August 2021) - Diprose, William K; Wang, Michael TMTM; Ghate, Kaustubha; Brew, Stefan; Caldwell, James R; McGuinness, Ben; Alan Barber, P
Abstract : Objective: To evaluate the safety and efficacy of intra-arterial thrombolysis (IAT) as an adjunct to endovascular clot retrieval (ECR) in ischaemic stroke, we performed a systematic review and meta-analysis of the literature. Methods: Searches were performed using Medline, Embase, and Cochrane databases for studies that compared ECR to ECR with adjunctive IAT (ECR+IAT). Safety outcomes included symptomatic intracerebral haemorrhage (sICH) and mortality at three months. Efficacy outcomes included successful reperfusion (Thrombolysis in Cerebral Infarction score of 2b to 3), and functional independence, defined as a modified Rankin Scale score of 0 to 2 at three months. Results: Five studies were identified that compared combined ECR+IAT (IA alteplase or urokinase) to ECR-only, and were included in the random effects meta-analysis. There were 1693 ECR patients, including 269 patients treated with combined ECR+IAT and 1424 patients receiving ECR-only. Pooled analysis did not demonstrate any differences between ECR+IAT and ECR-only in rates of sICH (OR: 0.61, 95% CI: 0.20-1.85; P=0.78), mortality (OR: 0.77, 95% CI: 0.54-1.10; P=0.15), or successful reperfusion (OR: 1.05, 95% CI: 0.52-2.15; P=0.89). There was a higher rate of functional independence in patients treated with ECR+IAT, although this was not statistically significant (OR: 1.34, 95% CI: 1.00-1.80; P=0.053). Conclusions: Adjunctive IAT appears to be safe. In specific situations, neurointerventionists may be justified in administering small doses of intraarterial alteplase or urokinase as rescue therapy during ECR.